2021
DOI: 10.1007/s10072-021-05607-2
|View full text |Cite
|
Sign up to set email alerts
|

Safinamide improves sleep and daytime sleepiness in Parkinson’s disease: results from the SAFINONMOTOR study

Abstract: Background and objective Some studies observed a benefit of PD patients after treatment with safinamide in some non-motor symptoms. Our aim was to analyze the effectiveness of safinamide on sleep and daytime sleepiness in Parkinson’s disease (PD) patients. Material and methods SAFINONMOTOR is a prospective open-label single-arm study conducted in 5 centers from Spain. In this analysis, a secondary objective of the study, the score in the Pittsburgh Sleep Quality Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Finally, a significant effect of safinamide on subjective sleep quality, sleep latency, sleep efficiency, and then on sleep disturbances was observed between baseline and follow-up. This finding concords with previous and preliminary reports about the effects of safinamide on sleep measured either objectively through polysomnographic recording or subjectively with different scales (Liguori et al 2018a , b ; Santos García et al 2021 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Finally, a significant effect of safinamide on subjective sleep quality, sleep latency, sleep efficiency, and then on sleep disturbances was observed between baseline and follow-up. This finding concords with previous and preliminary reports about the effects of safinamide on sleep measured either objectively through polysomnographic recording or subjectively with different scales (Liguori et al 2018a , b ; Santos García et al 2021 ).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the items related to sleep and fatigue, mood, apathy, attention and memory, gastrointestinal and urinary symptoms, and pain were significantly reduced at the follow-up (García et al 2021b ). Following this report, other results have been published from this multi-centre study, but separately analysed, documenting an improvement of sleep, daytime sleepiness, depression, and pain (García et al 2021a ; Labandeira et al 2021 ; Santos García et al 2021 ). Considering the importance of a comprehensive and prospective analysis including an homogeneous large sample of motor-fluctuating PD patients treated by safinamide as add-on treatment to LD, the present study collectively evaluated all these NMS at baseline and after 6 months of stable treatment in a group of sixty motor-fluctuating PD patients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Specifically reviewing individual parameters evaluated in the PDF-39, a distinct improvement can be seen in, for example, muscle cramps (item 37), joint pains (item 38) and unpleasant hot or cold sensations (item 39), and in the case of items 37 and 39 this difference is significant. Further clinical studies on pain symptoms have been initiated, some have already been concluded and confirm the positive effect (Grigoriou et al 2021 ; Santos Garcia et al 2021a , b ).…”
Section: Safinamidementioning
confidence: 93%
“…The so-called SAFINONMOTOR study was able to demonstrate positive effects on pain, sleep and mood (Grigoriou et al 2021 ; Laban Deira et al 2021 , Santos Garcia et al 2021a , b ). The improvement seen on sleep which was confirmed by another study focused on Rapid Eye Movement (REM) sleep behaviour disorders (Plastino et al 2021 ), exploring the clinical and video-polysomnographic changes occurred during safinamide treatment in 30 PD patients.…”
Section: Safinamidementioning
confidence: 99%